METODE PENDIDIKAN ANTI KORUPSI UNTUK ANAK BAGI ORANG TUA DI DESA PAPRINGAN MELALUI KOMIK DIGITAL - Aris Prio Agus Santoso; Winarti Winarti; Guritno Adi Nugroho; Hanzel Gustav Glorr (ABDI MAKARTI, 2023)
Anti-corruption education must be instilled in an integrated manner starting from the family. Education on anti-corruption from an early age can create children with a more reflective personality. Parents can do anti-corruption teaching through digital applications. Information and communication technology development makes it easier for humans to access information anytime and anywhere. One of the developments that can be utilized in education is the development of learning for children through Digital Comics. The method used to educate the public is through case studies, looking for digital comic references, and training in making digital comics and how to educate children. Based on the results of community service, it was found that parents in Papringan Village, Semarang Regency, had never provided Anti-Corruption Education at an early age at home. The obstacle for parents in giving anti-corruption education is that most parents are busy working, so there is no time to teach anti-corruption education from an early age from the family. After being given education through community service, there has been a significant change; parents have started downloading comics about anti-corruption, instilling anti-corruption personalities, and inviting children to discuss corruption cases.